Groups IV, V and VI metal oxide-containing hydrotalcite catalysts: state of the art on their catalytic applications - Valdivieso-Vera, Daniel A.; Guerrero-Pérez, María Olga (Elsevier, 2024)
The present contribution is a review paper that summarizes the structure, properties and catalytic applications of hydrotalcite based materials when they are modified by the incorporation of oxide metals from groups 4, 5 and 6. The unique properties of hydrotalcites, with a double layer structure able to host ions in the interlayer space and its basicity, together with the properties of transitions metal oxides from groups 4, 5 and 6, leads to materials highly promising as catalysts. The incorporation can form dispersed species of those oxides on the hydrotalcite-like structure, which acts as support, or by the incorporation of those elements into the hydrotalcite structure. The structure and properties of these materials have been reviewed and analyzed, in order to give a detailed description of the main factors that affect the catalytic properties of these interesting materials.
Keywords: Catalizadores; Óxidos metálicos; Ingeniería química; Hydrotalcite; Mixed-oxide catalysts; Magnesia; Alkali-doped catalysts; Basic solids